New horizons in bladder cancer research - Boormans, Joost L.; Zwarthoff, Ellen C.; Black, Peter C.; Goebell, Peter; Kamat, Ashish M.; Nawroth, Roman; Seiler, Roland; Williams, Stephen B.; Schmitz-Dräger, Bernd J. (Urologic Oncology-Seminars and Original Investigations, 2019)
The 16th Meeting of the International Bladder Cancer Network (IBCN) took place from October 11 to 13, 2018 in Rotterdam, the Netherlands. As in the previous year, muscle-invasive bladder cancer (MIBC) was the main topic of the congress based upon the rapid evolution in this field over the last several years. This year´s meeting was dominated by presentations focusing on genomic subtyping in MIBC and identification of novel therapeutic targets. These topics were complemented by submissions on immunotherapy, a variety of clinical topics, and biomarker research. Based upon the presentations, it may be concluded that the IBCN increasingly serves as an interdisciplinary forum not only for the presentation of work-in-progress covering all facets of bladder cancer research, but also for catalyzing the discussion of discrepant research findings in an effort to find consensus. The 16th Meeting of the IBCN took place from October 11 to 13th, 2018 in Rotterdam, the Netherlands, hosted by Ellen Zwarthoff and Joost Boormans. Approximately 120 participants gathered for another fully packed program displaying recent achievements in basic and clinical research covering the entire spectrum of bladder cancer. This year's meeting was dominated by presentations focusing on genomic subtyping and identification of novel therapeutic targets. These topics were complemented by submissions on immunotherapy, clinical topics, and biomarker research. Keynote lectures were delivered by G. Robertson (Canada) on MIBC genomics and the organizational challenges of the PanCancerAtlas project. Comprehensive information was provided on the Cancer Genome Atlas (TCGA) project including the structure of the consortium and the development and validation of molecular classification of MIBC. Results from the project suggest that regulons (groups of genes controlled by a common regulator) appear to be correlated with prognosis and may replace gene expression analysis in the future. M. Thelen (Switzerland) discussed the role of chemokines in cancer metastasization reporting on his research on the atypical chemokine receptor 3. The inaugural IBCN lecture was presented by M. Ingersoll (France) discussing gender disparities in development of adaptive immunity following Bacillus Calmette-Guerin therapy. In addition to the traditional “Industry meets IBCN” sessions, a format for discussion between industry representatives, researchers, and physicians in break-out groups, new formats were introduced—in the Oxford style of debate, P.J. Goebell (Germany) and W. Stadler (USA) delivered animated discussion on the appropriateness of urologists administering systemic immune checkpoint inhibitors. There was consensus that practice may differ between different health systems and countries, and educational/training background. In a second interesting discussion, D. McConkey (USA) and H. Al-Ahmadie (USA) debated if traditional histology will be replaced by molecular classification of bladder tumors. It was concluded that molecular classification offers valuable additional information but cannot yet replace traditional histology. Furthermore, the growing evidence of tumor heterogeneity in bladder cancer was discussed in a separate topic session. L. Dyrskjot discussed genomic and transcriptomic heterogeneity and their impact on clinical decision making. G. Sjödahl presented data on heterogeneity of molecular subtypes within the primary tumor and between the primary tumor and metastases, that is surprisingly limited. Y. Allory discussed spatial and temporal heterogeneity of bladder cancers particularly focusing on the basal-like phenotype. Due to the continued increase in the number of participants and abstract submissions, a poster session was implemented at this year´s meeting for the first time. Posters were briefly presented in the forum. Two travel awards were presented to H. Yamashita (USA) for his submission on peroxisome proliferator-activated receptor gamma-mediated repression of transcription factor activating protein 2 alfa expression identifying a transcriptional circuit in basal-squamous bladder cancer in a cell line model. S.B. Williams (USA) received his award for his registry-based analysis of outcome and costs in patients with localized MIBC undergoing either bladder sparing trimodal therapy or radical cystectomy. The latter was found to generate improved survival outcomes at lower costs as compared with trimodal therapy. The best presentation awards were presented to A. Kamoun (France) who discussed a consensus molecular classification for MIBC. The international demand for a consensus classification, already raised at previous meetings, has resonated with important players in this field. A potential consensus comprising 6 classes was proposed based upon a thorough analysis of the existing classifications. As an extension of the IBCN meeting a consensus conference on genomic classification of MIBC was held that included all major groups in this field. M. Garige (USA) received his award for a detailed examination of inhibitors of metabolic processes in bladder cancer cells before and after therapy. A take home message of the meeting was that the IBCN increasingly serves as an interdisciplinary forum not for the presentation of work-in-progress covering all facets of bladder cancer research, but also for catalyzing the discussion of discrepant research findings in an effort to find consensus. Exemplified may this also be by the fact that the efforts to unify the subclassification of MIBC had its nidus on the preceding meetings of the IBCN on this topic and brought together the various disciplines which ultimately were able to finalize their consensus work in a last concluding meeting directly following the IBCN. Thus, the IBCN meetings and the close cooperation of IBCN with its official journal, Urological Oncology, continue to provide a unique platform for exchange, discussing and intensifying multidimensional collaborations, thus finally satisfying the increasing need for answers regarding the management of bladder cancer patients. The 17th meeting of the IBCN will take place in Aarhus, Denmark, October 3 to 5, 2019.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Basic research; Bladder cancer; Clinical trials; International Bladder Cancer Network (IBCN); Molecular classifier; Tumor models